A multimodal analysis of graphic novels used in the Malaysian English language classroom / Thusha Rani Rajendra - Thusha Rani, Rajendra (2016)
Graphic novels remain an unchartered territory in the Malaysian curriculum. This study investigated how comics, visual and textual components are represented and cohesion realised in graphic novels from the genre of adapted classics. Additionally, the study discussed the pedagogical implications of deploying graphic novels in English Language classrooms. As a first, the study also focused on investigating adapted classics which are reprinted as graphic novels. The theoretical frameworks based on the works of Eisner (1985, 2008), McCloud (2004), Okum (2005), McKenzie (2005), Halliday (1994, 2004) and Kress and van Leeuwen (1996, 2006) were deployed. The graphic novels used were Black Beauty (2010), Journey to the Centre of the Earth (2010) and The Boscombe Valley Mystery (2009). Interviews were conducted with the writers, illustrators and an official from the Ministry of Education of Malaysia for triangulation. Results of the study show that both writers and illustrators of the novels adhered to certain linguistic and image structures to support the close adaptations of the original works. The comics conventions analysis indicates that critical considerations are made specifically on compression and extensions in recreating the original through sequential art. The linguistic analysis of transitivity reveals the dominance of three Processes: Material, Relational and Mental Processes. As such, the most active Participants are Actors, Goals, Sensers, Phenomenon, Tokens, Values, Carriers and Attributes. The type of Circumstance prevalent is Circumstances of Location. Additionally, Circumstances of Events provide an avenue to condense the time frame. There is also a predominance of Narrative Processes. The dominance of Action Processes denotes the focus on actions and movements to accentuate the dynamism of the characters. The use of Conceptual Processes demonstrates the reliance on images that are static. The findings affirm that Material Processes of SFL (representing linguistic functions) correspond with Narrative Processes of VG as both represent ‘outer experiences’ in a material world. In establishing cohesion, the use of splash pages provides a continuous background whereas overlap panels anchor continuous sequences clearly. The role of readers as interpreters is pertinent in establishing coherence through cognitive deduction. The analysis of Panel-to-Panel Transitions shows that Action-to-Action transitions are prevalent and this is parallel with most mainstream American comic books and graphic novels. This denotes that though the genre is different, the analysis reveals that mainstream transitions patterns are adhered to. The data analysis of Text Image Interaction discloses that the Complementary type of interaction is predominant. Colours are also utilised to create cohesion between the panels. The positions of speech balloons denote a clear distinctive cohesion marker through placements that support the reader to follow the Western convention of reading. Captions are utilised to create cohesion by providing information and narrative knowledge. Contrary to assumptions, the study unveils that the authors and illustrators of the three novels did not work together. Importantly, this study ascertains that both writers and illustrators of this genre relied on actions, both linguistically and visually represented, to support the abridgement of the originals. In the case of TBVM, this study establishes the fact that it should be considered a graphic reader rather than a graphic novel mainly due to its structural composition. Besides filling up the gap in research, the conceptual framework supports the effective dissection of these graphic novels through semiotics resources.